EXPLORING THE EFFICACY OF ART THERAPY ON EMOTIONAL AND COGNITIVE DEVELOPMENT IN CHILDREN IN INTERNALLY DISPLACED PERSONS CAMPS: A CASE STUDY FROM NASARAWA STATE, NIGERIA - Onuorah, Nwachukwu Akomaye; Orimaye, Jacob Oluwafemi; Bolarinwa, Joshua Olusegun (African Journal of Social and Behavioural Sciences, 2025)
Children in Internally Displaced Persons (IDP) camps in Nasarawa State, Nigeria, face significant emotional and cognitive challenges due to displacement-related trauma. While traditional interventions prioritize physical needs, psychological rehabilitation, like art therapy, remains underexplored. This study investigates the efficacy of art therapy as a tool for fostering emotional resilience and cognitive development in displaced children. Using a qualitative case study approach, data were collected from 30 children aged 6–15 through interviews, observations, and focus group discussions. Findings reveal that art therapy significantly enhances emotional expression, reduces anxiety, and improves problem-solving skills. Participants demonstrated increased self-esteem, emotional regulation, and social engagement. Additionally, cognitive benefits, including improved memory, concentration, and critical thinking, were observed. Caregivers and facilitators noted positive behavioural changes, reinforcing the therapeutic impact of art-based interventions. The study highlights the importance of integrating art therapy into IDP camp mental health frameworks, advocating for policy-driven support and culturally sensitive implementation. By providing an alternative, non-verbal mode of emotional expression, art therapy emerges as a critical psychosocial intervention for displaced children. Future research should investigate scalable models and potential challenges in implementing art therapy programs in various humanitarian settings.